KETAHANAN GALUR PADI IRBB TERHADAP PENYAKIT HAWAR DAUN BAKTERI DI KABUPATEN PURWAKARTA DAN SUBANG - Yuliani, Dini; Sudir, Sudir (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2022)
Planting rice resistant varieties to bacterial leaf blight (BLB) is a major component in controlling BLB disease, which is practical for farmers to implement. However, resistant varieties are constrained by the ability of pathogens that cause BLB disease to form new pathotypes of Xanthomonas oryzae pv. oryzae (Xoo) can break the resistance of rice varieties. This study aimed to evaluate the resistance level of IRBB rice lines to BLB in the field as parent material for crossbreeding resistant varieties to control BLB disease. The research was conducted in Cikadu village, Cibatu sub-district, Purwakarta district, and in Rancamahi village, Purwadadi sub-district, Subang district in the 2018 planting season. The results showed that two IRBB lines, namely IRBB 54 and IRBB 64, the Java 14 differential variety, and the new high yielding variety Inpari 32, consistently reacted highly resistant to BLB in Purwakarta. Three IRBB lines, namely IRBB 2, IRBB 54, IRBB 64, Java 14, and Inpari 32, consistently reacted high resistant to BLB in Subang. In Purwakarta, two types of Xoo were identified: pathotypes IV and VIII. While in Subang, one kind of Xoo was identified, namely pathotype VIII. The highly resistant and resistant varieties can be recommended as parent sources of resistant genes for the assembly of BLB resistant varieties, especially for the Xoo population of pathotypes IV and VIII in Purwakarta and Xoo pathotype VIII in Subang.